2013
DOI: 10.3390/molecules18055221
|View full text |Cite
|
Sign up to set email alerts
|

Changes in SeMSC, Glucosinolates and Sulforaphane Levels, and in Proteome Profile in Broccoli (Brassica oleracea var. Italica) Fertilized with Sodium Selenate

Abstract: The aim of this work was to analyze the effect of sodium selenate fortification on the content of selenomethyl selenocysteine (SeMSC), total glucosinolates and sulforaphane, as well as the changes in protein profile of the inflorescences of broccoli (Brassica oleracea var. Italica). Two experimental groups were considered: plants treated with 100 μmol/L sodium selenate (final concentration in the pot) and control plants treated with water. Fortification began 2 weeks after transplantation and was repeated once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In particular, selenate treatment increased the GSL content by 15.2% compared to the control. Previous studies reported that the total GSL content is minimally affected by selenate treatment in broccoli sprouts and mature broccoli (25 and 100 lmol/L) (Avila et al, 2013;Sepúlveda, Barrientos, Mahn, & Moenne, 2013). In the present study, the total GSL content was not affected after Se fertilization in cultivars FL60 and SL120, agreeing with previously reported values.…”
Section: Effects Of Control Selenite and Selenate Treatments On The supporting
confidence: 94%
See 2 more Smart Citations
“…In particular, selenate treatment increased the GSL content by 15.2% compared to the control. Previous studies reported that the total GSL content is minimally affected by selenate treatment in broccoli sprouts and mature broccoli (25 and 100 lmol/L) (Avila et al, 2013;Sepúlveda, Barrientos, Mahn, & Moenne, 2013). In the present study, the total GSL content was not affected after Se fertilization in cultivars FL60 and SL120, agreeing with previously reported values.…”
Section: Effects Of Control Selenite and Selenate Treatments On The supporting
confidence: 94%
“…In the present study, selenite and selenate treatments did not significantly influence the production of sulforaphane. The sulforaphane content in broccoli is minimally different between the control and selenate treatments (Sepúlveda et al, 2013). A similar result was also obtained in the present study for cultivar FL60.…”
Section: Effects Of Control Selenite and Selenate Treatments On The supporting
confidence: 89%
See 1 more Smart Citation
“…The plants responded to glycine supply by altering the expression of proteins involved in protein processing, amino acid metabolism and redox homeostasis. A similar experiment involving broccoli investigated the effect of supplying the plants with a non-limiting concentration of the essential trace element selenium ( Sepúlveda et al, 2013 ), resulting in an enhanced accumulation in the inflorescence of a number of proteins associated with the general stress response, while that of pathogen defense-related proteins was reduced. The effect of an organic farming regime on the cabbage proteome has shown that the cropping system had a measurable effect on the accumulation of proteins involved in glycolysis, the Krebs cycle, amino acid metabolism and various detoxification processes ( Nawrocki et al, 2011 ).…”
Section: Proteomicsmentioning
confidence: 99%
“…In addition, selenoglucosinolates displayed a higher anticarcinogenic activity than thioglucosinolates [162]. Se fertilization has been reported to exert no significant influence on glucosinolate levels in both broccoli sprouts [163][164][165] and florets [166]. Hence, Se fertilization is a good approach to accumulating selenium while maintaining glucosinolate content.…”
Section: Fertilizationmentioning
confidence: 99%